EXPERIENCES OF SOCIAL WORK ACADEMICS IN TURKEY DURING THE COVID-19 PANDEMIC - Meliha Döğücü; Ece Parlak Ünlü; Sinan Akçay (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study aims to explore and understand the effects of the Covid-19 pandemic on personal and professional lives of social work academics. Phenomenological approach was used in the study, which was designed with qualitative research method. Data were collected through semi-structured interviews with 23 social work academics who had lecturing experience before and during the Covid-19 pandemic. Thematic analysis method was used for the analysis of data. The following five main themes were determined as a result of the analysis: social work academics’ perception of Covid-19, effects of the pandemic on personal lives of social work academics, the challenges faced by social work academics in their professional lives due to the pandemic, the opportunities they found in their professional lives, and their search for new methods in field practicum.